Healthy lifestyle application - Chuah, Pei Jin (2018)
Obesity is one of the biggest health concerns in communities across the country. This may due to a variety of reasons such as genetics, lack of physical activity, the environment and poor diet. Nowadays, many people have their busy life and no enough time to prepare healthy meals, so they usually have their meals from fast food restaurants. This will lead them to get disease easily like high blood pressure, high cholesterol, heart disease, diabetes and certain type of cancers. To overcome this problem, this project proposes an application which it can help and motivate users in exercising and eating healthy foods. The objective to build this application is to evaluate BMI value and suggest the healthy meals to the users. Rapid Application Development (RAD) is the methodology used to develop this application. The RAD methodology consists of four main stages including requirements planning, user design, construction and cutover. After the application has been developed, the client is given a user acceptance test (UAT). The UAT testing will ensure that all functions in the application can run smoothly and fulfil all the objectives. In the conclusion, it is hoped that this project will benefit the interested user in their life.